PJMHS 2022
DOI: 10.53350/pjmhs22163421
|View full text |Cite
|
Sign up to set email alerts
|

Primary Headache among University Students: Across Sectional Study

Abstract: Background: Recent studies have shown an increase in prevalence of different types of headache among students all over the world. Objective: To determine the prevalence of, triggering and associated factors primary headaches among medical students with the aim of increasing awareness about this particular health issue. Participants and Methods: Descriptive cross-sectional study was conducted from September to December 2019 on 196 students, college of medicine, Northern Border University (NBU). Results: A one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…In our study, 33% described headaches as from one side while the remaining participants were on both sides of the head. This was comparable to a previous study that reported that frontal headache reported as the most common type of headache (24.1%) [19], nearly similar findings recorded by Shehata et al, in Saudi Arabia [20] and Nandha & Chhabra [21] in India.…”
Section: Resultssupporting
confidence: 91%
“…In our study, 33% described headaches as from one side while the remaining participants were on both sides of the head. This was comparable to a previous study that reported that frontal headache reported as the most common type of headache (24.1%) [19], nearly similar findings recorded by Shehata et al, in Saudi Arabia [20] and Nandha & Chhabra [21] in India.…”
Section: Resultssupporting
confidence: 91%
“…The questionnaires for this study were adopted from previous studies [ 15 , 16 , 23 ]. The study questionnaires were divided into three sections.…”
Section: Methodsmentioning
confidence: 99%
“…In Saudi Arabia, Almesned et al found a prevalence of 53.78% of headaches among medical students [ 15 ]. The prevalence was higher among pharmacy students, at 88.7% [ 16 ]. However, researchers at King Faisal University found a prevalence of 41.6% of headaches, and migraine prevalence was 58.4% [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Neurodegenerative diseases have been on the rise as people live longer, which explains this phenomenon. Due to reasons such as a shortage of medical professionals and infrastructure, developing countries bear a disproportionately high burden of traumatic neurologic illnesses (8) .…”
Section: Introductionmentioning
confidence: 99%